2022
DOI: 10.1177/23259582221109613
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, Effectiveness and Safety of Dolutegravir Based Antiretroviral Regimens among HIV Infected Children and Adolescents in Tanzania

Abstract: Objectives:This study aimed at assessing adherence, effectiveness, and safety of DTG-based HAART regimens among HIV-infected children and adolescents in Tanzania. Methods: This was a single-center prospective cohort study, conducted at the pediatric HIV Clinic in Mbeya, Tanzania. A binary logistic regression model was used to determine predictors of undetectable viral load at week 24. The results were significant when P-value was <0.05. Results: A total of 200 patients were enrolled with the majority (85.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Results are higher than those found in the NAMSAL trial (31%) (10) possibly because the trial used self-reports combined with pill count. Results are, however, consistent with a crosssectional study (11), and a prospective cohort in Tanzania (22).…”
Section: Prevalence Of Suboptimal Adherence To Dolutegravir-based Art...supporting
confidence: 86%
“…Results are higher than those found in the NAMSAL trial (31%) (10) possibly because the trial used self-reports combined with pill count. Results are, however, consistent with a crosssectional study (11), and a prospective cohort in Tanzania (22).…”
Section: Prevalence Of Suboptimal Adherence To Dolutegravir-based Art...supporting
confidence: 86%
“…A Tanzania cohort reported similar rates of children with a VL of <1,000 copies/mL: 84% after 1 year on DTG. 26 More ART-experienced children were unsuppressed pre-DTG (35%) compared to the Tanzania study which reported 18%. 26 Among children in 6 SSA countries, VLS after 12 months on DTG was 93%, though the cohort had a much higher VLS rate of 95% before DTG introduction than our cohort.…”
Section: Discussionmentioning
confidence: 84%
“…26 More ART-experienced children were unsuppressed pre-DTG (35%) compared to the Tanzania study which reported 18%. 26 Among children in 6 SSA countries, VLS after 12 months on DTG was 93%, though the cohort had a much higher VLS rate of 95% before DTG introduction than our cohort. 16 We are likely to have seen higher VLS among children on DTG in our study if we had higher suppression rates from the pre-DTG period as in these other studies.…”
Section: Discussionmentioning
confidence: 84%
“…In studies in Kenya and at Baylor sites in Botswana, Eswatini, Lesotho, Malawi, Tanzania, and Uganda [ 23 , 33 ], the authors reported viral suppression rates of 93.4–95.8% when applying a threshold of 1000 copies/ml, where in our study, 96.1% had a viral load less than 1000 copies/ml at 24 months. However, other studies have reported lower viral suppression rates after transition to dolutegravir (Mozambique: 76.2% [ 25 ]; Tanzania: 82.5% [ 34 ]), raising questions about the comparability of HIV programs and its populations in sub-Saharan Africa [ 35 ].…”
Section: Discussionmentioning
confidence: 99%